THE GLOBALIZATION OF MEDICAL SERVICES: TRENDS, CHALLENGES, AND OPPORTUNITIES - Chris G. Sorongon; Anik Yuesti (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
This study discusses the globalization of health care. The first part addresses the current situation of the global health order, emphasizing the changes that have occurred in the last half of the 20th century and that are now demanding regional or global responses. It further reviews the globalization of health care. Trade in health services is addressed in its four basic forms: (1) export of services; (2) the international movement of health care consumers; (3) the international movement of health care providers; (4) and the establishment of facilities in other countries. The globalization of medical services has surged in recent decades, characterized by cross-border patient mobility, evolving healthcare delivery practices, and technological advancements. It explores the multifaceted nature of this trend, emphasizing the rise of medical tourism, technological impacts, regulatory challenges, and ethical considerations. Through an extensive literature review and a mixed-methods approach involving qualitative interviews and quantitative surveys, we examine perspectives from patients, healthcare professionals, and policymakers. Findings reveal significant benefits, such as greater access to a broader range of treatments and cost savings, while also highlighting challenges related to healthcare quality, regulatory disparities, and ethical dilemmas surrounding medical tourism. The study concludes by advocating for harmonized regulations, improved patient education, and international collaboration to optimize the benefits of healthcare globalization while addressing its inherent risks. It also discusses the role of the World Trade Organization in the field of health care.